2003
DOI: 10.1080/jmf.14.2.85.90
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in umbilical cord blood: a simple and widely available clinical method to assess the risk of amniotic fluid infection and funisitis

Abstract: Umbilical cord plasma CRP concentrations were elevated in patients with amniotic fluid infection, congenital neonatal sepsis and funisitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 18 publications
1
55
2
Order By: Relevance
“…An increase of monocyte concentration was also observed. However, total white cell count and CRP did not seem useful in the diagnosis of intrauterine infection or fetal inflammation, although in other studies appreciable associations have been found 19 31. The numbers of mother–infant pairings studied here do not allow firm conclusions to be drawn although the colonised group did have decreased radiological evidence of RDS.…”
Section: Discussioncontrasting
confidence: 71%
“…An increase of monocyte concentration was also observed. However, total white cell count and CRP did not seem useful in the diagnosis of intrauterine infection or fetal inflammation, although in other studies appreciable associations have been found 19 31. The numbers of mother–infant pairings studied here do not allow firm conclusions to be drawn although the colonised group did have decreased radiological evidence of RDS.…”
Section: Discussioncontrasting
confidence: 71%
“…FIRS is associated with an increase in pro-inflammatory cytokines (e.g. IL-1β, TNF-α)[87], chemokine (IL-8)[54], and C-reactive protein [185] in umbilical cord blood, which may lead to short- and long-term complications in preterm neonates [21,55,57,58,67,86,87,89,185191]. On the other hand, as confirmed by the study herein, FIRS is also associated with an increased umbilical cord plasma concentration of IL-10 [192,193].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal fever during labor or delivery, premature rupture of fetal membranes, perinatal asphyxia and other problems not resulting from infection were found to be associated with elevated CRP levels in umbilical cord blood [21]. However, it has recently been demonstrated that CRP levels in umbilical cord plasma at birth are increased in neonates with sepsis, funisitis, or who were born to mothers with microbial invasion of the amniotic cavity [22].…”
Section: C-reactive Proteinmentioning
confidence: 97%